Abd al-Razzāq Kāshānī: His Life, Works and Contribution to Sufism - Hashtroodi, Fatemeh (Jurnal Usuluddin, 2015)
Kāshānī is one of the most influential Sufi authors of later Islamic history. He wrote disseminated commentaries and important treatises, both in Arabic and Persian, which are rooted in Ibn al-ʻArabī’s ontological discourse. His works made him one of the great exponents and promoters of the School of Waḥdah al-Wujūd of Ibn ʻArabī after Ṣadr al-Dīn Qūnawī and advocates the intellectual discipline and School of Shaykh Akbar. His simple, scholarly manner used to explain and classify Ibn ʻArabī’s teaching. His remarkable esoteric interpretation, Ta’wīlāt al-Qurān; although compatible with Ibn al-‘Arabī’s basic world view, there are important differences of perspective that mark Kāshānī as an independent thinker. His commentary on Fusūs al-Ḥikam, in which he discusses about the matter of Waḥdah al-Wujūd, promoted Ibn ‘Arabī’s teaching into the Persian speaking world.